Mental health and its relationship to occupational stresses of the information specialist in university libraries (University of M’sila Libraries as a Model) - LAMINE, Nassira; BOUNIF, Mohamed Lamine (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
This study aims to identify the nature of the relationship between mental health and occupational pressures at university libraries information specialists, as well as to identify the level of both mental health and occupational pressures they have, as well as to identify the differences between the sexes in the study variables. The sample of the study consisted of (40) information specialists in the libraries of the University of Messila. To achieve the objectives of the study, the researchers used both the modified mental health scale (SCL-90-R) and the occupational stress scale of the researcher Gourari Hanan (2014) using the correlational descriptive approach. The two researchers also used the program (SPSSV24) to verify the psychometric properties (stability by Cronbach's alpha and half-segmentation, as well as validity via Pearson's internal consistency). As for the hypotheses of the study, the following statistical methods were used: - A test (T) for one sample to compare the arithmetic means. - Pearson correlation coefficient between scores of the two measures of mental health and occupational stress. - (T) test for two independent samples to compare the characteristics of the sample (gender) with the degrees of the two scales. The following results were reached: - The level of mental health of the respondents is average. - The level of occupational pressure among respondents is high. - There are differences between respondents in mental health depending on the gender variable. - There were no differences between the subjects in the occupational settings depending on the gender variable